2017
DOI: 10.1016/j.jpainsymman.2017.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French Version of the Edmonton Symptom Assessment System

Abstract: The F-ESAS is a valid and reliable tool for measuring multidimensional symptoms in French-speaking patients with an advanced cancer. All forms of F-ESAS performed well with a trend for better psychometric performance for F-ESAS-NU, but patients preferred the F-ESAS-VE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… a Quality of Life at the End of Life: QUAL-E [25] b Edmonton Symptom Assessment: ESAS [26] c Support Team Assessment Schedule: STAS [27] d EORTC Quality of Life of Palliative Cancer Patients: EORTC QLQ-C15-PAL [28] e McGill Quality of Life Questionnaire-Revised: MQOL-R [29] f M. D. Anderson Symptom Inventory: MDASI [30]…”
Section: Results: Findings and Challenges From The French Translationmentioning
confidence: 99%
“… a Quality of Life at the End of Life: QUAL-E [25] b Edmonton Symptom Assessment: ESAS [26] c Support Team Assessment Schedule: STAS [27] d EORTC Quality of Life of Palliative Cancer Patients: EORTC QLQ-C15-PAL [28] e McGill Quality of Life Questionnaire-Revised: MQOL-R [29] f M. D. Anderson Symptom Inventory: MDASI [30]…”
Section: Results: Findings and Challenges From The French Translationmentioning
confidence: 99%
“…Assessment of distressing symptoms was performed using a modified Edmonton Symptom Assessment Scale (ESAS) 19. For the purpose of this study, we excluded the assessment of symptoms that had already been shown not to be conducive to art therapy: emesis, drowsiness, lack of appetite and breathlessness.…”
Section: Methodsmentioning
confidence: 99%
“…This instrument was the one with the most representation in terms of number of studies, 15 in total (Carvajal et al, 2011; Carvajal et al, 2013; Chinda et al, 2011; Claessens et al, 2011; Gretarsdottir et al, 2016; Hannon et al, 2015; Kwon et al, 2013; Mori et al, 2018; Nekolaichuk et al, 2017; Paiva et al, 2015; Pautex et al, 2017; Philip et al, 1998; Sprague et al, 2018; Tricou et al, 2019; Yokomichi et al, 2015). All the psychometric properties were measured, except for measurement error and criterion validity.…”
Section: Psychometric Propertiesmentioning
confidence: 99%
“…In the initial Rasch model, a person separation index of =0.77 was shown, which indicated a satisfactory reliability, but the general fit of the model was poor (X2 = 155.41; p < 0.01) and all the elements showed disordered thresholds (Sprague et al, 2018). Internal consistency was rated as ‘inadequate’ or ‘very good’ for all the studies where it was present (Carvajal et al, 2011, 2013; Chinda et al, 2011; Gretarsdottir et al, 2016; Hannon et al, 2015; Kwon et al, 2013; Mori et al, 2018; Paiva et al, 2015; Pautex et al, 2017; Yokomichi et al, 2015) and obtained values for Cronbach's alpha >0.70 in all of them. The psychometric reliability property was rated as ‘doubtful’ or ‘very good’ for all the studies where it was evaluated.…”
Section: Psychometric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation